Pan-American Guidelines for the treatment of SARS-CoV-2/COVID-19: a joint evidence-based guideline of the Brazilian Society of Infectious Diseases (SBI) and the Pan-American Association of Infectious Diseases (API) - Barbosa, Alexandre Naime [UNESP]; Chebabo, Alberto; Starling, Carlos; Pérez, Clevy; Cunha, Clóvis Arns; de Luna, David; Nunes, Estevão Portela; Zambrano, Gabriela; Ferreira, Juliana Carvalho; Croda, Julio; Falavigna, Maicon; Gomes-da-Silva, Monica Maria; et al. (Springer Nature, 2023)
Background: Since the beginning of the COVID-19 pandemic, therapeutic options for treating COVID-19 have been investigated at different stages of clinical manifestations. Considering the particular impact of COVID-19 in the Americas, this document aims to present recommendations for the pharmacological treatment of COVID-19 specific to this population. Methods: Fifteen experts, members of the Brazilian Society of Infectious Diseases (SBI) and the Pan-American Association of Infectious Diseases (API) make up the panel responsible for developing this guideline. Questions were formulated regarding prophylaxis and treatment of COVID-19 in outpatient and inpatient settings. The outcomes considered in decision-making were mortality, hospitalisation, need for mechanical ventilation, symptomatic COVID-19 episodes, and adverse events. In addition, a systematic review of randomised controlled trials was conducted. The quality of evidence assessment and guideline development process followed the GRADE system. Results: Nine technologies were evaluated, and ten recommendations were made, including the use of tixagevimab + cilgavimab in the prophylaxis of COVID-19, tixagevimab + cilgavimab, molnupiravir, nirmatrelvir + ritonavir, and remdesivir in the treatment of outpatients, and remdesivir, baricitinib, and tocilizumab in the treatment of hospitalised patients with severe COVID-19. The use of hydroxychloroquine or chloroquine and ivermectin was discouraged. Conclusion: This guideline provides recommendations for treating patients in the Americas following the principles of evidence-based medicine. The recommendations present a set of drugs that have proven effective in the prophylaxis and treatment of COVID-19, emphasising the strong recommendation for the use of nirmatrelvir/ritonavir in outpatients as the lack of benefit from the use of hydroxychloroquine and ivermectin.
Keywords: COVID-19; Guidelines; SARS-CoV-2; Therapy; Treatment